Network Analysis of Eating Disorders Symptoms Co-occurring With Impulsive Personality Traits and Negative Mood States in Patients With Bulimia Nervosa - Chen, Yan; Guo, Lei; Wu, Mengting; Zhang, Lei; He, Qianqian; Zheng, Yuchen; Wu, Lin; Zheng, Hui; Chen, Jue (Frontiers in Psychiatry, 2022)
Background Bulimia nervosa (BN) is characterized by recurrent episodes of eating large amounts of food without control. Studies have found positive correlations of BN symptoms with impulsive traits and negative affect. However, the network relationship supporting BN symptoms is unclear. Methods The study participants included female BN patients (146) and healthy controls (HCs, 146). The participants were matched for age. All participants completed the Eating Disorder Examination Questionnaire 6.0, Barratt Impulsiveness Scale-11, Beck Anxiety Inventory, and Beck Depression Inventory. We characterized the centrality parameters of BN, impulsiveness, and anxiety and depression symptoms of BN patients compared with HCs. Results Among all symptoms in the constructed BN group network, Shape dissatisfaction had the highest strength. In the BN group network, three clusters of symptoms (“ED-specific symptoms,” “impulsivity,” and “anxiety and depression”) were linked to each other by several symptoms. Compared to the HC network, impulsiveness was strongly associated with Concerns about Others Seeing One Eat in the BN network. Conclusion This study shows that ED-specific symptoms, i.e., Shape dissatisfaction, play a key role in BN. The cognition of “shape dissatisfaction” is a basis, and impulsivity and emotional symptoms are maintaining factors that may lead to BN development.